Organizational commitment, organizational justice and employee turnover in Malaysia - Ponnu, C.H.; Chuah, C.C. (Academic Journals, 2010)
This study attempts to investigate the relationship among organizational justice, organizational commitment and turnover intention of Malaysian employees. Using a sample of 172, collected from employees across organizations in the country, both procedural and distributive justice perceptions were significant contributors in explaining organizational commitment and turnover intention. These findings have important implications for managers in formulating appropriate strategies, policies and procedures to improve employees' commitment to their organizations and to reduce their turnover intentions.